2014
DOI: 10.1097/brs.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of Incidental Durotomy in Spine Surgery

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 19 publications
1
23
1
Order By: Relevance
“…However, Nandyala et al 36 and McMahon et al 37 both reported a signifi cant increase in neurological deficits after ID. We found no signifi cant differences in reoperation rates due to ID ( P = 0.187, data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…However, Nandyala et al 36 and McMahon et al 37 both reported a signifi cant increase in neurological deficits after ID. We found no signifi cant differences in reoperation rates due to ID ( P = 0.187, data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Based on a Nationwide Inpatient Sample database, Nandyala et al reported longer hospitalization and a greater incidence of preoperative complications including hematoma and neurological injury [27] in patients with an incidental durotomy, which may increase hospital resource utilization and costs. Similarly, our study revealed a significantly longer hospitalization period in the Dura?…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] To date, the effect of increased BMI as an independent risk factor for incidental durotomy has not been established. [27][28][29][30] To date, the effect of increased BMI as an independent risk factor for incidental durotomy has not been established.…”
Section: Discussionmentioning
confidence: 99%